The Correlation Between Reading Anxiety and Reading Comprehension in Junior High School Students - Amanda Aprilia Wulandari (Retain: Journal of Research in English Language Teaching, 2025)
This research investigates the relationship between students' reading anxiety and their reading comprehension. A quantitative correlational design was employed to analyze the data collected from 38 students at one of the private junior high schools in Gresik. The study used a questionnaire adapted from the English Foreign Language Reading Anxiety Inventory (EFLRAI) and a reading comprehension test adapted from students’ textbooks. Data analysis techniques were carried out using IBM SPSS Statistics 26. Through this research, the researcher found that the majority of students' reading anxiety was at a medium level. The results also indicated a strong negative and significant correlation between reading anxiety and reading comprehension, with a Pearson Product Moment Correlation coefficient of -0.755 and a p-value of 0.000. The findings suggest that students with higher reading anxiety tend to have lower reading comprehension, while those with lower reading anxiety tend to have higher reading comprehension. The study contributes to the understanding of the impact of reading anxiety on students' reading abilities.